Administrative Data Based Population and Household Estimates for Scotland - Rowley, David; Ellis, Caroline; Macintyre, Tom (International Journal of Population Data Science, 2025)
Objectives The Administrative Data Based Population Estimates (ABPEs) are estimates of the usual resident population of Scotland, produced solely using administrative data. The Administrative Data Based Household Estimates (ABHEs) are estimates of the number of households in Scotland, using similar data. Methods Several administrative datasets were linked together, including those from health, education and the electoral register. The records were resolved into individuals to produce the Administrative Data Record Set. This was trimmed down using activity-based business rules to a set of individuals (Scotland’s Integrated Demographic Dataset, SIDD) believed to be usual residents on the reference date. The ABPEs are then taken to be the count of individuals on the SIDD. Estimates for households can then be produced by grouping SIDD individuals who appear at the same address on the administrative data. Results The ABPEs for 2016 to 2022 have been compared with the corresponding official Mid-Year Estimates (MYEs) and Scotland’s Census 2022 estimates. The ABPE total is 0.22% lower than the Census 2022 estimate. Differences are larger by Local Authority (LA), although for all but one LA the ABPE is within the census 95-per cent LA confidence interval target of 3%. In each year, the ABPE is closer to the MYEs that have been rebased using Census 2022 estimates, than the original MYEs are. The ABHEs are on average 6.8% lower than the rebased household estimates, and around 7.1% below the Census 2022 estimate. The ABHEs have fewer smaller (one or two person) households and more larger (three or more person) households than the official estimates. Conclusion The ABPEs perform well in comparison with the original MYEs, when benchmarked against the rebased MYEs and the census estimates. Differences by LA suggest greater uncertainty than the census achieves. As address information is not available for all administrative data records, the ABHEs are lower than official estimates.